2017
DOI: 10.1039/c6cy01904h
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanism of dimethyl ether carbonylation to methyl acetate over mordenite – a combined DFT/experimental study

Abstract: Dimethyl ether carbonylation to methyl acetate over mordenite was studied theoretically with density functional theory calculations and experimentally in a fixed bed flow reactor. A new reaction path to methyl acetate entirely in the 8 membered ring was discovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 52 publications
8
77
0
Order By: Relevance
“…The calculation results revealed that a feasible reaction temperature and pressure exist in the range 573-598 K and 50-65 bar, respectively ( Figure 6). Although different from the condition for DME carbonylation reported in literature (usually below 450 K and 20 bar [20,21]), the finding seemed to be compatible with our test condition. comparable to or a little higher than those of any hybrid/bifunctional catalysts reported in literature (cf.…”
Section: Attempts To Improve the Selectivity To Dmesupporting
confidence: 78%
See 1 more Smart Citation
“…The calculation results revealed that a feasible reaction temperature and pressure exist in the range 573-598 K and 50-65 bar, respectively ( Figure 6). Although different from the condition for DME carbonylation reported in literature (usually below 450 K and 20 bar [20,21]), the finding seemed to be compatible with our test condition. comparable to or a little higher than those of any hybrid/bifunctional catalysts reported in literature (cf.…”
Section: Attempts To Improve the Selectivity To Dmesupporting
confidence: 78%
“…The calculation results revealed that a feasible reaction temperature and pressure exist in the range 573-598 K and 50-65 bar, respectively ( Figure 6). Although different from the condition for DME carbonylation reported in literature (usually below 450 K and 20 bar [20,21]), the finding seemed to be compatible with our test condition. The activity test was performed in a dual-bed catalyst system using the SP-derived catalyst and zeolite ferrierite (FER@FER) recently developed by a seed method [22], where the latter catalyst of 2.0 g was placed right after the bed of 0.6 g SP-60 or SP-80 ( Table 5).…”
Section: Attempts To Improve the Selectivity To Dmesupporting
confidence: 78%
“…Theoretical studies have been employed to calculate reaction free energy barriers of possible initiation and C-C coupling steps to shed light on plausible reaction mechanisms [43][44][45][46][47][48][49][50][51][52][53][54][68][69][70]. Using H-SSZ-13 as the catalyst we recently proposed a viable mechanism of the initiation reaction based on DFT calculations that have been corrected using second order Møller Plesset perturbation theory (MP2) [71] thus comprising highly accurate reaction barriers [72].…”
Section: Supplementary Informationmentioning
confidence: 99%
“…We postulate that the non-linearity in these rates as a function of Si/Al originates from the sensitive relationship between MA rates and methoxy location, as evidenced by prior experimental and computational work in MOR. 6,9,17,43 This relationship arises from the stabilization (or lack thereof) via confinement of the transition state formed by CO attack on the methoxy group, which decreases (or increases) the activation barrier of the RDS. There are three primary positions for monovalent, extraframework cations to site in SSZ-13 ( Figure 7) associated with the crystallographically-distinct O atoms.…”
Section: Cha: Activity Vs Si/almentioning
confidence: 99%